Bioproducts generation from carboxylate platforms by the non-conventional yeast Yarrowia lipolytica. Issue 6 (28th August 2021) - Park, Young-Kyoung; González-Fernández, Cristina; Robles-Iglesias, Raúl; Vidal, Lea; Fontanille, Pierre; Kennes, Christian; Tomás Pejó, Elia; Nicaud, Jean-Marc; Fickers, Patrick
ABSTRACT: In recent years, there has been a growing interest in the use of renewable sources for bio-based production aiming at developing sustainable and feasible approaches towards a circular economy. Among these renewable sources, organic wastes (OWs) can be anaerobically digested to generate carboxylates like volatile fatty acids (VFAs), lactic acid, and longer-chain fatty acids that are regarded as novel building blocks for the synthesis of value-added compounds by yeasts. This review discusses on the processes that can be used to create valuable molecules from OW-derived VFAs; the pathways employed by the oleaginous yeast Yarrowia lipolytica to directly metabolize such molecules; and the relationship between OW composition, anaerobic digestion, and VFA profiles. The review also summarizes the current knowledge about VFA toxicity, the pathways by which VFAs are metabolized and the metabolic engineering strategies that can be employed in Y. lipolytica to produce value-added biobased compounds from VFAs. Abstract : A review on the use of organic wastes as renewable sources to generate volatile fatty acids by anaerobic digestion and on their bioconversion into added-value compound by Yarrowia lipolytica .